2021
DOI: 10.32598/jams.24.4.620.4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors of Musculoskeletal Pain in Students of Engineering and Humanities Faculties of Arak University in 2018-2019

Abstract: Background and Aim: The aim of this study was to investigate the prevalence and associated factors of musculoskeletal pain in undergraduate students of Engineering and Humanities Faculties of Arak University in 1397-98. Methods & Materials: This cross-sectional study of 464 students (humanities, 169 and engineering, 295 people) with mean age (20.56+1.51 years), Body Mass Index (22.29±3.35 kg/m2)). Was done at the undergraduate level of Arak University in the 2018-2019 years. Nordic questionnaire to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…The significant prevalence of musculoskeletal pain, specifically in the lower back region, among students in various disciplines, has been well-documented in previous research. Studies have shown that students in fields like engineering, humanities, sports, and physical education, often report high incidences of spine pain, including LBP, due to factors such as prolonged sitting and specific physical activities related to their field of study (13,15). In line with these findings, our study also underscores the impact of physical and lifestyle factors on LBP prevalence.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The significant prevalence of musculoskeletal pain, specifically in the lower back region, among students in various disciplines, has been well-documented in previous research. Studies have shown that students in fields like engineering, humanities, sports, and physical education, often report high incidences of spine pain, including LBP, due to factors such as prolonged sitting and specific physical activities related to their field of study (13,15). In line with these findings, our study also underscores the impact of physical and lifestyle factors on LBP prevalence.…”
Section: Discussionsupporting
confidence: 87%
“…The total score is then expressed as a percentage, with higher scores indicating greater disability. Disability levels were categorized as minor (5)(6)(7)(8)(9)(10)(11)(12)(13)(14), modest (15)(16)(17)(18)(19)(20)(21)(22)(23)(24), severe (25-34), and complete (35-50). The Oswestry Disability Index (ODI) has demonstrated good test-retest reliability, with an Intraclass Correlation Coefficient (ICC) ranging from 0.72 to 0.98, and a Cronbach's alpha value of 0.89, reflecting excellent internal consistency (10,11).…”
Section: Methodsmentioning
confidence: 99%